Criminal Law Enforcement Against Perpetrators of Environmental Pollution in The Criminal Justice System in Indonesia - Aa Muhamad Zaenudin; Kristiawanto Kristiawanto; Maryano Maryano (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
This study aims to analyze the effectiveness of criminal law in addressing environmental pollution in Indonesia and to explore the concept of an ideal environmental criminal law enforcement framework for the future. This study applies a normative legal research method to obtain relevant data concerning the issues under investigation. The data used in this research come from secondary data sources and tertiary legal materials. Additionally, primary data are utilized to support the legal materials obtained from secondary sources. The data analysis is conducted using a qualitative juridical analysis method. This research employs John Rawls’ theory of justice and the theory of law enforcement. The findings of this study indicate that, despite efforts to enforce criminal law against environmental polluters, the sanctions imposed often fail to create the expected deterrent effect. Law enforcement still encounters challenges, such as conflicts between economic interests and environmental protection, weak legal culture, as well as limitations in infrastructure and evidence gathering. To enhance its effectiveness, a more comprehensive approach is required, integrating restorative and preventive approaches along with the application of the principle of distributive justice. The restorative approach focuses on victim and environmental recovery through alternative dispute resolution mechanisms, while the preventive approach, through administrative supervision, aims to prevent violations from occurring. Additionally, strengthening legal awareness through public education and enhancing collaboration among law enforcement agencies, such as the Ministry of Environment, the police, and the prosecutor's office, are essential steps in establishing a more effective and just environmental criminal law enforcement system.